Women Regional Heads and Gender-Responsive Policies in Tabanan Regency, Bali, Indonesia - Ratnawati Ratnawati; Oberlin Silalahi (Green Publisher Indonesia, 2022)
This study examined the contribution of women's government heads to gender-responsive policies at the local level. It was carried out due to the increase in the number of women leaders in various countries as heads of government at the national and local levels in the 21st century, which contributed to the realization of gender-responsive policies. This paper argues that the social capital owned by women regional heads contributes to realizing gender-responsive policies. This study was carried out using the focus group discussions (FGD) methodology, with data collected from 19 key informants through in-depth interviews and documents. The result showed that the success of women regional heads in realizing gender-responsive policies is influenced by their social capital in the form of material capital, access to information with organizations and public officials, and the provision of a network capital that is bonding, bridging, and linking. Furthermore, there are other factors, namely personal capacity related to knowledge and understanding of gender-responsive policies, involvement and experience of women regional heads in organization activities, and support politics of the regional parliament/DPRD. This study provides insight for women willing to advance in the election contestation process by considering their previous experience and involvement in political activities as essential factors in realizing gender-responsive policies.